2020
DOI: 10.1007/s10851-020-00960-x
|View full text |Cite
|
Sign up to set email alerts
|

Cortical-Inspired Wilson–Cowan-Type Equations for Orientation-Dependent Contrast Perception Modelling

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(46 citation statements)
references
References 56 publications
(106 reference statements)
3
43
0
Order By: Relevance
“…In [ 44 , 45 , 46 ], a variant of the Wilson-Cowan (WC) model based on a variational principle and adapted to the geometry of V1 was employed to model the neuronal activity and generate illusory patterns for different illusion types. The modelling considered in these works is strongly inspired by the integro-differential model firstly studied in [ 47 ] for perception-inspired Local Histogram Equalisation (LHE) techniques and later applied in a series of work, see, for example, [ 48 , 49 ] for the study of contrast and assimilation phenomena.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In [ 44 , 45 , 46 ], a variant of the Wilson-Cowan (WC) model based on a variational principle and adapted to the geometry of V1 was employed to model the neuronal activity and generate illusory patterns for different illusion types. The modelling considered in these works is strongly inspired by the integro-differential model firstly studied in [ 47 ] for perception-inspired Local Histogram Equalisation (LHE) techniques and later applied in a series of work, see, for example, [ 48 , 49 ] for the study of contrast and assimilation phenomena.…”
Section: Introductionmentioning
confidence: 99%
“…The modelling considered in these works is strongly inspired by the integro-differential model firstly studied in [ 47 ] for perception-inspired Local Histogram Equalisation (LHE) techniques and later applied in a series of work, see, for example, [ 48 , 49 ] for the study of contrast and assimilation phenomena. By further incorporating a cortical-inspired modelling, the authors showed in [ 44 , 45 , 46 ] that cortical Local Histogram Equalisation (LHE) models are able to replicate visual misperceptions induced not only by local contrast changes, but also by orientation-induced biases similar to the ones in Figure 2 . Interestingly, the cortical LHE model [ 44 , 45 , 46 ] was further shown to outperform both standard and cortical-inspired WC models and was rigorously shown to correspond to the minimisation of a variational energy, which suggests more efficient representation properties [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, these equations have been coupled with the neurogeometric model of V1 to great benefit. For instance, in [4][5][6] they allowed replicating orientation-dependent brightness illusory phenomena, which had proved to be difficult to implement for non-cortical-inspired models. See also [39] for applications to the detection of perceptual units.…”
Section: A Rotated Sound Image Corresponds To a Completely Different mentioning
confidence: 99%
“…As in the case of V1 [8], we model neuronal connections via these dynamics. In practice, this amounts to assuming that the excitation starting at a neuron X 0 = (ω , ν ) evolves as the stochastic process {A t } t≥0 naturally associated with (6). This is given by the following stochastic differential equation:…”
Section: The Neuronal Interaction Kernelmentioning
confidence: 99%